Synthesis, characterisation and photophysical studies of oxadiazolyl coumarin: A new class of blue light emitting fluorescent dyes. (May 2017) - Matta, Akanksha; Bahadur, Vijay; Taniike, Toshiaki; Van der Eycken, Johan; Singh, Brajendra K.
Abstract: A library of novel 1, 2, 4-oxadiazole linked coumarin dyes have been synthesised via condensation of corresponding acid6 and N '-hydroxybenzimidamide8 . This new class of organic compounds were examined for their fluorescent properties and found to emit blue light in the visible region of the spectrum with very high Stoke's shift values. Most of these compounds demonstrated high quantum yields and fluorescence life time in nano -second range which makes them quite lucrative to be used as new fluorescent probes. The highest quantum yield of 0.68 was shown by compound9j which also shows high Stoke's shift value. The electronic structure of these coumarin-based donor–π–acceptor (D–π–A)-type organic dyes have been examined by Density Functional Theory (DFT). TGA analysis of few of the compounds show that they are stable up to temperature range of 0–245 °C. The synthesised compounds were characterised by NMR and mass spectrometry and the structure of two of these compounds have been confirmed by X-ray crystallography. Highlights: Synthesis and photophysical studies of novel blue light emitting oxadiazolyl coumarin dyes. Development of a new coumarin-based chromophore with Oxadiazole ring at 4-position of coumarin. Good fluorescence efficiency makes them quite lucrative for their applications in fluorescent labelling, probes, OLED's.